Strategies for transcending the chaos of societal disruptions. Issue 1 (13th October 2020) - Camillus, John C.; Baker, Jeffrey E.; Daunt, Anushka I.; Jang, Jungyoon
Abstract : Purpose: This study aims to offer a strategic management response to societal disruptions of the magnitude triggered by the agricultural, industrial and information revolutions. These pose challenges that are much greater and different in kind than the industry-wide disruptions that businesses have learned to manage. Pandemics, climate change, biotech and artificial intelligence guarantee that such societal disruptions will be an inescapable and recurring reality. Design/methodology/approach: The paper builds on the strategic management responses to wicked problems, which possess in microcosm the chaotic ambiguity that characterizes societal disruptions. Findings: The authors propose a management process that affirms a sense of identity, identifies robust actions, adopts a real-options approach and uses a platform organization. Research limitations/implications: The primary limitation is that the recommendations and findings are extrapolations of organizational practices in analogous situations. No examples of formal management processes specifically designed to address societal disruptions were identified. Practical implications: The practical implications are significant. The specific recommendations in the paper directly address strategic management practice in organizations. Social implications: The social implications are integral to the motivation of the paper as it describes the intrinsic characteristics of societal change and transformation, enabling organizations to interact with society on a dynamic basis. Originality/value: While there has been growing interest and research into business and industry disruptions, the challenge of societal disruptions, which is the focus of this paper, has not been directly addressed.